A feasibility study on disaster preparedness in regional and rural emergency departments in New South Wales: Nurses self-assessment of knowledge, skills and preparation for disaster management. (March 2020) - Brewer, Catherine A.; Hutton, Alison; Hammad, Karen S.; Geale, Sara K.
Abstract: Background: Nurses who work in regional and rural hospitals face unique challenges to disaster preparedness and response. Geographical location and isolation, decreased resources and subsequent workforce, along with organizational and financial restraints are some of the hurdles these individuals and communities face [1, 2]. Method: The Disaster Preparedness Evaluation Tool was applied a population of Regional and Rural Emergency Nurses in New South Wales. Result: Thirty-two nurses participated in this study. Their level of disaster preparedness was at a moderate level for knowledge, skills and preparation for disaster management. Their experiences broadly mirrored those found in earlier research. Conclusion: Results highlighted the nature of and delivery of continuing professional development in relation to disaster preparedness; mechanisms to encourage emergency department nurses to develop personal and family preparedness plans (to improved disaster preparedness); increased training in relation to psychological assessment of patients, and identification of biological agent signs and symptoms.